2022
DOI: 10.3390/s22155671
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter-Wave Radar Localization Using Indoor Multipath Effect

Abstract: The positioning of indoor electronic devices is an essential part of human–computer interaction, and the accuracy of positioning affects the level of user experience. Most existing methods for RF-based device localization choose to ignore or remove the impact of multipath effects. However, exploiting the multipath effect caused by the complex indoor environment helps to improve the model’s localization accuracy. In response to this question, this paper proposes a multipath-assisted localization (MAL) model bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Comparing the results mentioned in Section II with the findings in [17] and [15], it is evident that our approaches yielded a similar level of accuracy. In [17], the authors achieved positioning accuracy ranging from 16cm to 3.25m using the AoA technique in an open space while the authors of [15] demonstrated an accuracy of 15cm. Despite the fact that we were operating in a more cluttered environment, we achieved an accuracy of 16cm, which is comparable to the aforementioned works.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Comparing the results mentioned in Section II with the findings in [17] and [15], it is evident that our approaches yielded a similar level of accuracy. In [17], the authors achieved positioning accuracy ranging from 16cm to 3.25m using the AoA technique in an open space while the authors of [15] demonstrated an accuracy of 15cm. Despite the fact that we were operating in a more cluttered environment, we achieved an accuracy of 16cm, which is comparable to the aforementioned works.…”
Section: Discussionsupporting
confidence: 55%
“…The results indicate that positioning accuracy using a single sensor reaches submeter levels in 95% of cases and is less than 0.4m in 60% of cases. The richness of multipath components in mmWave systems is also exploited in [15] which introduces a multipathassisted localization (MAL) model based on mmWave radar for indoor electronic device localization. This model effectively incorporates multipath effects when describing reflected signals, enabling precise target position determination using the MAL area formed by the reflected signal.…”
Section: Related Workmentioning
confidence: 99%
“…The single-bounce scattering is directly reflected by the target. The multi-bounce scattering is reflected between the target, ground and wall more than once [25][26][27][28].…”
Section: Radar Slant Range Of Multiple Bounce Scattering Characteristicmentioning
confidence: 99%
“…Radar electromagnetic scattering may be multiple-bounce in closed spaces such as indoors and in tunnels scattering is directly reflected by the target. The multi-bounce sc between the target, ground and wall more than once [25][26][27][28].…”
Section: Radar Slant Range Of Multiple Bounce Scattering Characteristicmentioning
confidence: 99%
“…For instance, the authors of [ 23 ] conducted AoA and signal measurements in a 35 m by 65.5 m open space and achieved a position accuracy ranging from 16 cm to 3.25 m. Positioning research using this mmWave technology is still in very early stages but early theoretical findings and some practical experiments demonstrate its strong potential to achieve the very high accuracy required by modern smart applications. The authors in [ 107 ] propose a multipath-assisted localization (MAL) model based on millimeter-wave radar to achieve the localization of indoor electronic devices. The model fully considers the help of the multipath effect when describing the characteristics of the reflected signal and precisely locates the target position by using the MAL area formed by the reflected signal.…”
Section: Technologies For 3d Localizationmentioning
confidence: 99%